Attracting and maintaining the Y generation in nursing: A literature review - Hutchinson, D.; Brown, Janie; Longworth, K. (Blackwell Publishing, 2012)
Objective: This paper explores the literature related to attracting the Y Generation (Y Gen: people born between 1980 and 2000) to the nursing profession and retaining them in our current workforce. Design: A comprehensive review of the literature supported the need for further research. Three searches were conducted and all relevant literature was reviewed by each researcher. Literature included in the review was chosen based on specific search-term inclusion. Data source: Structured searches were conducted with no limitations on publication type, date or language. Search engines used included: Australian Family and Society, CINAHL, Expanded Academic, Google Scholar, Medline, ProQuest and PubMed. Results: A critical review of the literature, particularly empirical work on the subject has informed decision making regarding the research questions that remain to be explored. Conclusions: The literature revealed that the Y Gen is currently contributing to the nursing workforce demographics. Much discussion exists surrounding the integration of the Y Gen into the workplace along with the other three generations of nurses. There is also an abundance of descriptions of the Y Gen characteristics and values. There is, however, limited reference relating to what attracted this generation to nursing or what might retain them in the nursing workforce.Implications for nursing management: The Y Gen is the largest generation to enter our workforce since the Baby Boomers. Health services need to recognize the needs of the Y Gen nurses and develop strategies to move the profession forward by preparing the current workforce and environment for a generation that is already here. The focus should be on their strengths with development made to structure a workforce that will support the Y Gen in their professional nursing role. Understanding what attracts the Y Gen to nursing, what managers can do to retain the Y Gen in nursing and how the nursing profession can support the Y Gen to assume a role in nursing and nursing governance will ensure that the retiring generation has left the nursing profession in capable hands.